Inclusion of Lycium barbarum, Psidium guajava, Momordica grosvenori and Garcinia mangostana in yogurt and their effects on fermentation and exopolysaccharide-production / Elham Bagheri - Bagheri, Elham (2012)
Yogurt is popularly consumed because of its high digestibility, refreshing organoleptic properties and the healthy bacteria it contains. Milk incubated with starter culture (SC) at 41⁰C in the presence of plants (Momordica grosvenori, Psidium guajava, Lycium barbarum or Garcinia mangostana) water extract were studied to examine the effects on acidification, microbial growth, gelation and exopolysaccharide (EPS) content. Initial pH values (5.8-6.2) of the mixture of milk, plant water extract and SC were not different (p>0.05) from control (6.20; mixture of milk and SC). The rates of pH reduction for all herbal-yogurts (-0.40 pH unit/ hour), except G. mangostana and M. grosvenori (-0.33 and -0.32 respectively pH unit/hr) was similar to control (-0.43 pH unit/ hr) during the first 4 hours of incubation. Microbial mass increased for both Lactobacillus spp. and Streptococcus thermophilus in the presence of plant water extracts at 0.75%, 1.5% and 3% (w/v). Lactobacilus spp. counts in L. barbarum-, P. guajava- and M. grosvenori- yogurts (1.52, 1.32 and 1.23 × 106 cfu/ ml, respectively, p>0.05) with the exception of G. mangostana- yogurt (0.69 × 106 cfu/ml; p>0.05) were higher compared to control (1.01 × 106 cfu/ ml). The S. thermophilus counts in L. barbarum-, P. guajava- and M. grosvenori- yogurts (785, 1045 and 805 × 106 cfu/ ml respectively, p>0.05) with the exception of G. mangostana- yogurt (610 × 106 cfu/ml; p>0.05) were higher than that in control (615 × 106 cfu/ ml). The EPS content in G. mangostana-yogurt (113.1 μg/ ml, p>0.05) was lower whereas L. barbarum-, P. guajava- and M. grosvenori- yogurts (181.4, 258.7 and 183.9 μg/ ml respectively, p<0.05 for P. guajava -yogurt only) were higher than control (132 μg/ ml). Syneresis (S) was increased in P. guajava- but decreased in G. mangostana-yogurts (3.61 and 2.90% respectively; p>0.05) whereas water holding capacity (WHC) was reduced in P. guajava (22.8%; p>0.05) but increased in G. mangostana (28.1%; p<0.05) compared to control (S= 3.23%, WHC= 24.1%). In summary, the presence of plant water extracts affected yogurt fermentation by modifying of yogurt bacteria growth and metabolism which resulted in the enhancement of acidification of yogurt.